Inflfluence of the use of Social-Media and Exposure to Pornography on the Sexual Behaviour of youths in selected tertiary institutions in Southwest Nigeria - Oladipupo Samuel Olaleye; Ademola Johnson Ajuwon (New Prairie Press, 2022)
Exposure to pornography is fraught with health and social implications. In Nigeria, there is a dearth of information on how youths have been exposed to pornography on social media (SM) and the effects of this on their sexual behaviors (SB). This study described the pattern of SM use, exposure to pornography, and the effects of this exposure on SB of young persons in southwest Nigeria. Two hundred students were randomly selected from two tertiary institutions. Data were collected using a pre-tested questionnaire that explored the respondents' SM usage pattern, exposure to pornography, and SB. Data were analyzed using descriptive statistics, Chi-square, and logistic regression. The mean age of respondents was 21.4±2.7. The SM in which most of the respondents had accounts were WhatsApp (96.7%) and Facebook (95.3%). Major sexual-related activities undertaken on SM included watching/ downloading naked pictures (7.0%) and sex videos (13.5%). A majority (92.5%) of the respondents have been inadvertently exposed to pornography, and the major sources of this exposure were SM (59.3%) and web-based Internet pages (61.5%). While only 68.0% have been intentionally exposed, the major sources of exposure were SM (42.3%) and web-based Internet pages (53.3%). About half (48.5%) have experienced sexual intercourse, out of which 17.5% reported having multiple sexual partners. Recent inadvertent (OR: 4.5, 95%CI: 1.25-16.4) and intentional (OR: 2.3, 95% CI: 1.2-4.8) exposure to pornography were significantly associated with the experience of sexual intercourse. Likewise, recent intentional pornography exposure was significantly associated with having multiple sexual partners (OR: 3.0, 95%CI: 1.1-8.6). SM use with exposure to pornography had notable effects on SB of young persons. Effective interventions should be conducted to reduce this exposure and its associated effects among the target population.